Upaya Pengawas dalam Meningkatkan Kompetensi Guru Menyusun RPP Kurikulum 2013 melalui Metode Coaching di MTs N 9 Sleman dan MTs Ibnu Sina Berbah - Rudi Astomo (Jurnal Pendidikan Madrasah, 2018)
This research aims to know the extent to which the success of the coaching methods of coaching competence models as a teacher in drawing up the implementation plan of learning especially RPP Curriculum year 2013. To know the competency of teachers in enhancing business assembles RPP K-13 through a coaching method conducted supervisor at MTsN 9 Sleman and MTs Ibnu Sina Berbah Sleman Yogyakarta. This research uses research methods of action. This research was carried out in MTsN 9 Sleman and MTs Ibnu Sina Berbah on February – April 2017. This research took place in three cycles. The results showed an increase in the competence of teachers through methods of coaching by coaches under the guidance of supervisor at MTsN 9 Sleman and MTs Ibn Sina. Then after the performance of supervision through the method of coaching which further attested by the existence of the data observations from the initial findings prior to coaching for MTsN 9 Sleman which originally was 34.52% and once implemented Coaching for 3 cycles then retrieved the value of observations 86.29%. So with the method of coaching coaching there is an increase in 51.77%. Whereas in MTs Ibn Sina, on the initial findings of the observation value obtained 34.56%. And having held coaching for 3 cycles obtained the value of observations 86.39%. So there is an increase of 51.83%.